EFEKTIVITAS MEDIA BERGAMBAR DAN PENYULUHAN METODE CERAMAH TANYA JAWAB (CTJ) TERHADAP PERILAKU MAKAN, AKTIVITAS FISIK DAN POLA TIDUR REMAJA UNDERWEIGHT TAHUN 2019 - ecy kartika sari; Zahtamal Zahtamal; Nurlisis Nurlisis; Novita Rany; Winda Septiani (STIKes Al-Insyirah Pekanbaru, 2019)
Underweight or lack of weight is state of being caused by the lack of energy intake compared with the amount og eergy expended. A lack of energy intake or consumption of essential nutrients needed by the body can be lowered activity was done by teenager. The result of the preliminary survey they that were undertaken in the senior high school 13 and 1 At Pekabaru, would be in the low teens 33 should be run as soon as many as 20 a teenager slipped to only their second underweight. The study aims to know about the effectiveness of media pictorial and counseling with the methods talk question and answer to behavior eat, physical activity dan sleep patterns undeweight teenagers in 13 and 1 Senior High School At Pekanbaru City. the kind of research used is (quasi experiment) with nonequivalent group pre-test post-test design. The Research is done at the July 2019. The population in this research is the entire fourth grade VII, VIII and IX. Use sampling tehniques is non random sampling. Instrumen on the study using by questionnaires, and data anlysis be done in univariat and bivariat. The results of study by test wicolxon and Mann Whitney test, and showed there were differences in the effectiveness of the pictorial media and counseling on question and answer lectures on changes in eating behavior, physical activity and sleep patterns of underweight adolescents in 13 and 1 Senior High School At Pekanbaru City. Schools should provide adequate outreach facilities such as picture books and powerpoints. So that counseling can be carried out smoothly and without obstacles. References : 49 References (2010-2016)